Spatial differences in the accumulation of elements by the lichen Cladonia rangiferina L. in the Pasvik Nature Reserve - Vladimir Elsakov; Alexander Novakovskiy; Natalia Polikarpova (Proceedings of the Karelian Research Centre of the Russian Academy of Sciences, 2018)
Nature Reserve and its surroundings (the Murmansk Region). The most significant factor influencing the accumulation of elements is the distance to non-ferrous metal industry facilities (industrial sites of the Kola Mining and Metallurgic Company (Kola MMC) of the Norilsk Nickel Holding). The exponential function proved to be well fit for this dependence. The elements fall into two groups: 1) elements present in the plant’s emissions and having a pronounced spatial gradient in the nature reserve and its surroundings (Cr, Fe, Co, Cu, Ni, Cd, Pb, As), and 2) elements which have no clear patterns in the distribution and depend on the “background” values (Zn, Mn and Hg). The concentrations of group 1 pollutants in the lichen decreased at a rate of 2–5 % for each kilometer of distance from the source of emissions. The content of most of the elements significantly (p < 0.05) correlated with each other. The exception was Mn, whose content was inhibited by an increase in the concentrations of other metals (primarily Pb, Fe, Co). Even samples with the lowest Ni, Cu, Co and Cd content from the sites furthest away from the source in the Pasvik Reserve and its surroundings had the elements concentrations higher than the environmental ‘background’ for adjacent tundra communities (Kanin tundra, Nenets Autonomous District). Lichens of the Pasvik Reserve accumulate higher concentrations of the main pollutants (Ni, Cu, Co and Fe) than vascular plants in the same territory. Graphic isopleths of the distribution of potential contaminant concentrations in lichen thalli were plotted for the territory of the reserve. The Pasvik Nature Reserve was used as the example to demonstrate that, at present, ecosystem components within protected areas cannot be regarded as geochemical standards for the regional environment due the regional atmospheric transfers from nearby industrial facilities.